IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 7 TAHUN 2019 TENTANG PELAYANAN ADMINISTRASI KEPENDUDUKAN SECARA DARING PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LABUHANBATU - Mukhsin Juniardo Siregar; Maya Jannah; Risdalina Siregar; Nimrot Siahaan; Indra Kumalasari M (Jurnal Ilmiah Advokasi, 2021)
The identity of the population is the basic thing that a person must have, in order to make it easier for people to socialize and interact with each other. Technological developments that occur at this time can facilitate the management and public administration services in the field of population and civil registration so that it is very efficient. The type of research used is Normative Empirical. Types of data sources in this study using three types of data sources, namely primary, secondary, and tertiary data. The data collection technique used by the author is Literature Study, Interview, and Documentation. The data analysis technique used is qualitative, comprehensive, and complete analysis. The results showed that the implementation of the online service regulations carried out by the Labuhanbatu Regency Population and Civil Registration Service was the first step for the community to register through the Whatsapp contact provided by the relevant agency. Then, enter the full name. Family card, and so on. Finally, the data that has been sent by the public will be automatically entered into the database for verification and management. The positive impact of the rules in the midst of the Covid-19 pandemic is that people no longer have to come to the office and crowd there to manage their respective interests, this makes the contact and transmission of the Covid-19 virus more minimal. The obstacles that occur in implementation in the field are that there are still many people who do not understand online registration because of limited ability to use technological advances such as the internet and how to overcome solutions in filing problems in managing Population and Civil Registration documents in Labuhanbatu Regency.Keywords: Service, Administration, Population, Civil RegistrationÂ